Preferensi penggunaan sumber informasi oleh mahasiswa dalam menyelesaikan tugas kuliah - Heriyanto Heriyanto (Jurnal Kajian Informasi dan Perpustakaan, 2020)
A wide range of information sources is available to students in various forms providing opportunities for students to utilize these information sources for study purposes. However, studies on the extent to which students know and use it to complete lecture assignments are still rare. This study aimed to identify undergraduate students' experience at one faculty in a university in Semarang when exploring various kinds of information resources to do their assignments. This qualitative study used interviews as the only technique in obtaining data. By employing purposive sampling method, eleven undergraduate students who met the specific criteria participated in this study. All the participants were interviewed using a semi-structured interview. The data were then analyzed by using thematic analysis, to uncover the undergraduate students’ information sources preference and how they used them. The findings revealed students’ selections of information sources for conducting their information retrieval process. They also identified the complexity of student information retrieval activities that were heavily affected by external factors such as the type of assignment, and internal from the students themselves, for example, knowledge of available information sources and motivation to use them. The findings provided evidence to inform the development of library services and information literacy responses to enhance undergraduate students learning.